2015
DOI: 10.1007/s12206-015-0435-0
|View full text |Cite
|
Sign up to set email alerts
|

Analytical determination of size-dependent natural frequencies of fully clamped rectangular microplates based on the modified couple stress theory

Abstract: This paper presents an analytical and size-dependent model for vibrational analysis of fully clamped rectangular microplates. Modified couple stress theory (MCST) and the Kirchhoff plate model are considered, and Hamilton's principle is employed to derive the sizedependent equation of motion that accounts for the effect of residual stresses. The natural frequencies of the microplate are extracted analytically by extended Kantorovich method. The present findings are validated with the available results in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…It is worth noting that this important conclusion has also been reported numerically by Tsiatas [19] and analytically by Askari and Tahani [20] …”
Section: Theoretical Formulationssupporting
confidence: 80%
See 1 more Smart Citation
“…It is worth noting that this important conclusion has also been reported numerically by Tsiatas [19] and analytically by Askari and Tahani [20] …”
Section: Theoretical Formulationssupporting
confidence: 80%
“…[20]). It has been shown that continuing the present procedure would leads to the convergence of the results which is so rapid and usually occurred after the second iteration step [20].…”
Section: Application Of the Ekmmentioning
confidence: 99%
“…Jomezadeh et al [28] performed a vibration analysis of rectangular Kirchhoff micro plates using a Levytype solution method. Askari and Tahani [29] employed the extended Kantorovich method to analyze the vibration behavior of a Kirchhoff micro plate. They presented the results for a fully clamped micro plate.…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of transverse shear and effects of boundary supports on the mechanical responses of plates are significant, it appears from the literature review that there is no analytical solution for micro plates having different boundary conditions and being modeled within shear deformation plate theories in conjugation with MCST. Even though a Levy-type solution [27,28,36], or the extended Kantorovich method [29] has been implemented to analyze Kirchhoff micro plates, the governing equations within the first order or higher order micro plate theories are solved using just the Navier method [32][33][34][35] or numerical methods [23,31,39]. That is, to the best of authors' knowledge, analytical solutions within shear deformation micro plate theories are available for just simply-supported ones.…”
Section: Introductionmentioning
confidence: 99%
“…The Modi ed Couple Stress Theory (MCST) bene ts from two main advantages of the inclusion of symmetric couple stress tensor and involvement of only one material length-scale parameter. Based on the modi ed couple stress theory, di erent studies have been conducted concerning vibrational behavior of micro-plates [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%